"Doomed by the Confusion in Their Design": Racialized Urban Space, Redlining, and Monolithic Whiteness in Paule Marshall's Brown Girl, Brownstones. (3rd June 2022) - Beckett, Balthazar I
Abstract: While Paule Marshall's novel Brown Girl, Brownstones (1959) has long been celebrated as a pivotal text in the canon of Caribbean American and African American women's literature, not enough attention has been paid to the material conditions underlying the coming-of-age story of her main protagonist, Selina Boyce. A close reading of the novel's engagement with urban space—in particular with the changes that Brooklyn's Bedford-Stuyvesant neighborhood undergoes in the late 1930s and early 1940s—reveals not only that the text contains an astute critique of American race formation at one of its most crucial moments, namely in the context of the New Deal's policies of redlining and white flight, but also that Marshall ought to be considered as an early, but important, voice of both critical race theory and whiteness studies.